2011
DOI: 10.1186/1745-6215-12-166
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of miltefosine alone and in combination with sodium stibogluconate and liposomal amphotericin B for the treatment of primary visceral leishmaniasis in East Africa: study protocol for a randomized controlled trial

Abstract: BackgroundTreatment options for Visceral Leishmaniasis (VL) in East Africa are far from satisfactory due to cost, toxicity, prolonged treatment duration or emergence of parasite resistance. Hence there is a need to explore alternative treatment protocols such as miltefosine alone or in combinations including miltefosine, sodium stibogluconate (SSG) or liposomal amphotericin B. The aim of this trial is to identify regimen(s) which are sufficiently promising for future trials in East Africa.Methods/DesignA phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 16 publications
(19 reference statements)
0
42
1
Order By: Relevance
“…Several successful reports on adjunct therapy of antimony with other drugs for treatment of leishmaniasis have been published (22)(23)(24)(25)(26). The antileishmanial efficacy of miltefosine, the only available oral drug, was also found to be enhanced when given in combination with paromomycin or an immunomodulator, picroliv (17,18,27).…”
Section: Discussionmentioning
confidence: 97%
“…Several successful reports on adjunct therapy of antimony with other drugs for treatment of leishmaniasis have been published (22)(23)(24)(25)(26). The antileishmanial efficacy of miltefosine, the only available oral drug, was also found to be enhanced when given in combination with paromomycin or an immunomodulator, picroliv (17,18,27).…”
Section: Discussionmentioning
confidence: 97%
“…SSG, ampB, and miltefosine have all been evaluated as combinatorial therapies for VL in the clinic (Musa et al, 2012; Omollo et al, 2011). Sundar et al have shown that combinations of sub-optimal anti-leishmanial compounds have the potential to be a more efficacious treatment with fewer side effects, however, combinatorial therapies using compounds that clear infections through non-host-mediated mechanisms are still at risk for cultivating resistant strains (Sundar et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by this new treatment approach, an exploratory study with miltefosine alone and combinations of single dose of L-AmB (10 mg/kg) with SSG (20 mg/kg) for 10 days and L-AmB (10 mg/kg) with miltefosine for 10 days is being done in East Africa. 179 …”
Section: Review Of Antileishmanial Agentsmentioning
confidence: 99%